Between adhesions and threats: The 1964 Coup in Senador Pompeu-CE - Martins, Antônio Wesley do Nascimento (Em Perspectiva, 2024)
This work reflects on some issues related to the 1964 Coup from Senador Pompeu, a town located in the Sertão Central of Ceará, through the analysis of historical sources such as a newspaper article collected in the Hemeroteca of the National Digital Library (BNDigital), Minutes present in the collection of the City Council (ACM-SP), excerpts from interviews present in the memorial book Paróquia de Nossa Senhora das Dores – 80 anos servindo ao Senhor (1999), as well as oral sources produced through interviews based on Thematic Oral History. In addition to contributing to the urgent and necessary fight against denialism regarding the topic by not only discussing it, but also expanding its reflection from a regional focus different from the so-called "Large centers," it is concluded that, due to the mobilization of the anti-communist imaginary of the period, there was sincere and ambiguous support for the victory of the coup coalition in the county. At the same time, other subjects, especially those associated with some social activities conducted by the Parish, suffered direct or indirect threats and persecution. Therefore, we dialogue with the theoretical framework of Motta (2021), Napolitano (2020; 2021), Presot (2010), Laborie (2010), Grynszpan (2007), Le Goff (1990), Luca (2008), Pollak (1989; 1992), among others.